Model Dukungan Holistik terhadap Pendidikan Anak di Pondok Pesantren - Dimas Pahlawanita Damayanti (LP. Ma'arif Janggan Magetan, 2023)
This study aims to assess the significance of parental support within the context of Islamic boarding schools (pondok pesantren) and explore various models of support that can be applied. The research approach employed in this study is a comprehensive review of existing literature (Library Research). The findings of this study indicate the pivotal role of parental support within the pondok pesantren environment in facilitating the development of the students (santri). In this regard, several models of support can be implemented, including emotional, social, economic, and participatory support. Each model of support plays a distinct role in aiding santri to achieve improved academic performance and promote positive personal development. The impact of parental support on santri is highly significant, with students who receive adequate support tending to have higher levels of happiness and stronger motivation for learning. This support also helps santri overcome various challenges and obstacles that may arise during their stay in the pesantren. Furthermore, the importance of open communication between parents and santri within the pesantren cannot be understated. Such communication contributes to the creation of an environment that supports the holistic development of santri. Effective communication allows parents to better understand the needs of their children and helps santri feel more comfortable in the pesantren environment.